Vegetables as a Source of Dietary Fiber to Prevent Degenerative Diseases - Deddy Muchtadi (Jurnal Teknologi dan Industri Pangan, 2001)
For long time vegetables were thought only as sources of several vitamins; however, it has been shown that vegetables contain other component, which is also important for maintaining body's health, i.e., dietary fiber. Dietary fiber is a group of polysaccharides oan other polymers, which cannot be digested by upper gastro-intestinal system of human. Dietary fiber can be grouped as soluble and insoluble dietary fiber, showing in different physiological effect. Soluble dietary fiber (SDF) is effective in preventing cardiovascular disease, while insoluble dietary fiber (IDF) can prevent the development of colon cancer, diverticulosis as well as obesity.Local vegetables found to contain high SDF (higher than 3,06% db) are: watercress, green bean, carrot, eggplant, lettuce, broccoli, spinach, string bean, and aubergine; while which contain high IDF (higher than 40,60% db) are: winged bean, watercress, chinese leaves, katuk leaves, lettuce, green bean, broccoli, carrot and spinach. Cooking (i.e. boiling, steaming and pan frying) decrease the IDF content of vegetables, while their SDF content is not affected by cooking treatments.